2016
DOI: 10.3352/jeehp.2016.13.12
|View full text |Cite
|
Sign up to set email alerts
|

How many schools adopt interviews during the student admission process across the health professions in the United States of America?

Abstract: Health profession schools use interviews during the admissions process to identify certain non-cognitive skills that are needed for success in diverse, inter-professional settings. This study aimed to assess the use of interviews during the student admissions process across health disciplines at schools in the United States of America in 2014. The type and frequency of non-cognitive skills assessed were also evaluated. Descriptive methods were used to analyze a sample of interview rubrics collected as part of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 4 publications
0
31
0
Order By: Relevance
“…Partly due to concerns about inter-interviewer reliability, many schools have replaced TIs with Multiple Mini-Interviews (MMIs), in which applicants work through a series of brief, semi-structured assessment stations, each attended by a different trained rater [ 3 , 11 ]. Single-school studies examining the MMI in isolation suggest the approach yields moderate to high inter-rater reliability (range of Cronbach’s alphas reported 0.65–0.98; range of G coefficients reported 0.55–0.72), and predicts aspects of subsequent academic performance [ 3 , 12 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Partly due to concerns about inter-interviewer reliability, many schools have replaced TIs with Multiple Mini-Interviews (MMIs), in which applicants work through a series of brief, semi-structured assessment stations, each attended by a different trained rater [ 3 , 11 ]. Single-school studies examining the MMI in isolation suggest the approach yields moderate to high inter-rater reliability (range of Cronbach’s alphas reported 0.65–0.98; range of G coefficients reported 0.55–0.72), and predicts aspects of subsequent academic performance [ 3 , 12 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The CanMEDS framework, for example, stresses the importance of communicative, collaborative and leadership skills [7]. The role of such skills is further emphasised by the Word Health Organization that identified them as essential prerequisites for effective interprofessional care [8,9]. Consequently, recent expert reports in Germany recommend social skills to be taught and evaluated in the course of the medical curriculum [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…1,7,13,17,18 In addition, not all programs use interviews to the same extent that our program does although for U.S. medical schools the use of interviews increased from 35% in 2009 to 86.4% in 2016. 19,20 Glazer et al's study published in 2016 reported that, in the U.S., 97.2% of pharmacy schools and 88.3% of dental schools, but only 19.7% of nursing schools and 15.4% of public health schools used interviews. 20 The much lower use of interviews by public health and nursing schools is interesting.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Glazer et al's study published in 2016 reported that, in the U.S., 97.2% of pharmacy schools and 88.3% of dental schools, but only 19.7% of nursing schools and 15.4% of public health schools used interviews. 20 The much lower use of interviews by public health and nursing schools is interesting. Glazer et al suggest that more students are admitted to nursing programs than other types of programs, requiring more resources, and that at some nursing programs applications may be prescreened by the home institution, possibly decreasing the number of criteria examined by the nursing program.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation